THE APPLICATION OF UML IN THE PROTOTYPE OF DESIGN EXPERT SYSTEM FOR THE DIAGNOSIS OF CHILI DISEASES AND PESTS - Muliadi Aziz; Irwan Budiman; Antar Sofyan (Lambung Mangkurat University, 2018)
Prototype or archetype is the initial form or standard size of an entity. In the design field, a prototype is made before it is developed or precisely made specifically for development before it is made on an actual scale or before mass produced, it will feel very difficult if you do not have a compounding model to design a system. Therefore, to design a prototype expert system for diagnosing diseases and pests of chilli plants using the Unified Modeling Language (UML) method. The purpose of the implementation of this model is to meet all user needs for the software to be built. Manfaat dari model ini dapat membantu perancang perangkat lunak dalam membangun sistem pakar untuk mendiagnosis penyakit dan hama tanaman cabai. The result of this UML implementation is to obtain use case of system processing, diagram activity, entity relationship diagram, and form input output design.